2004
DOI: 10.1186/1465-9921-5-17
|View full text |Cite
|
Sign up to set email alerts
|

Add-on therapy options in asthma not adequately controlled by inhaled corticosteroids: a comprehensive review

Abstract: Many patients with persistent asthma can be controlled with inhaled corticosteroids (ICS). However, a considerable proportion of patients remain symptomatic, despite the use of ICS. We present systematically evidence that supports the different treatment options. A literature search was made of Medline/PubMed to identify randomised and blinded trials. To demonstrate the benefit that can be obtained by increasing the dose of ICS, dose-response studies with at least three different ICS doses were identified. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 119 publications
2
44
0
2
Order By: Relevance
“…Combination therapy with LABA and inhaled corticosteroids reduces the frequency of exacerbations in asthma, and it is also efficacious as an interventional therapy in asthma exacerbations (16)(17)(18). In this study, SAL was able to suppress the production of TSLP in NHBE cells, and we also demonstrated the synergistic suppression of poly(I:C)-induced TSLP production by DEX and SAL in NHBE cells.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Combination therapy with LABA and inhaled corticosteroids reduces the frequency of exacerbations in asthma, and it is also efficacious as an interventional therapy in asthma exacerbations (16)(17)(18). In this study, SAL was able to suppress the production of TSLP in NHBE cells, and we also demonstrated the synergistic suppression of poly(I:C)-induced TSLP production by DEX and SAL in NHBE cells.…”
Section: Discussionsupporting
confidence: 56%
“…A suppressive effect of glucocorticoid on the expression of TSLP induced in airway epithelial cells by stimulation with the TLR3 ligand and Th2 cytokines was reported (14). In addition, several clinical studies showed that the combination of an inhaled corticosteroid and long-acting b-adrenergic agonist (LABA) is more efficacious in asthma than either alone, and reduces exacerbations (15)(16)(17)(18). We investigated the effects of dexamethasone (DEX) and salmeterol (SAL) on the induction of TSLP by poly(I:C).…”
Section: Clinical Relevancementioning
confidence: 99%
“…250 Kankaanranta and colleagues 250 aimed to review systematically the evidence that supports different treatment options for asthma, including increasing the dose of ICS, and the use of add-on therapy options such as a LABA, leukotriene antagonist or theophylline. Jarvis and Faulds 249 evaluated the therapeutic efficacy of FP at doses ഛ500 µg/day, and included comparisons with placebo, nonsteroidal, anti-inflammatory agents, other ICS drugs (BDP, BUD, flunisolide and triamcinolone acetonide), and combination with SAL.…”
Section: Other Systematic Reviewsmentioning
confidence: 99%
“…The number of participants was not reported in either review. Participants included in the reviews were adults or adolescents (one review 250 defined adolescents as aged >12 years) with mild to moderate asthma 249 or asthma that was inadequately controlled with ICS 250 (results are reported for patients with mild and moderate to severe asthma).…”
Section: Kankaanranta and Colleaguesmentioning
confidence: 99%
“…nhaled corticosteroids are the mainstay of asthma therapy, but there is now compelling evidence that addition of a long-acting inhaled b 2 -agonist (LABA; salmeterol or formoterol) gives better control in terms of reduced symptoms, improved lung function and reduced exacerbations in patients with mild, moderate and severe persistent asthma than increasing the dose of corticosteroids in patients not fully controlled on low doses [1][2][3][4][5]. This has led to the development of fixed combination inhalers, fluticasone/salmeterol (Seretide2/Advair2, GlaxoSmithKline), and budesonide/formoterol (Symbicort1, AstraZeneca), which are now increasingly used in asthma management [6,7].…”
mentioning
confidence: 99%